Analysis of Tax Audit Policy Implementation in Indonesia View from the Principle of Equality between Taxpayer and Fiscus - Inasito, David Osvaldo; Rosdiana, Haula (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Tax revenue is improving from year to year. This improvement can be seen in percentage trend of tax acceptance donation for APBN. Tax Examining is one of tax administration part, related to increase tax payer obedience, thing that always be criticized because of the closest relation with society, in this case, as an examined taxpayer. Society evaluates the work and quality of officers at Tax General Directorate as non-professional and tends to count on power.  The objective of this thesis writing is to compare examining tax in Indonesia with United States of America and Japan, analyzing problems relating to tax examining policy implementation in Indonesia, describing equality principles between tax payer and fescues in examining and describing the efforts which have been done by Tax General Directorate in handling inequality between tax payer and tax officer. Research approach is qualitative approach through analysis descriptive research. Data collecting technique through bibliography study and filed study by participants’ observation and interview with related parties. From study, result obtains equality policy of tax examinig in Indonesia compared with USA and Japan, although there is also some advantageous of tax policy in those nations. Basis principles in equality between tax payer and fescues in the examinig such as public trust, fair play, etiquette, right, and duty protection of tax payer, good governance, supervising and policy of whistle blowing. Critics of tax examinig policy implementation in Indonesia appear because of tax policy is not implemented wholly by tax observer and weaknesses of sanction-given to tax officers who broke the rule. Inequality also appears because the existence of examining policy is not ruled specifically in the rule and regulation. Tax General Directorate has done many efforts such as implementation of modern tax administration and the newest tax examinig rules such as forming Observers Team and Tax Examinig Questioners. The efforts will face some weaknesses if it is not supported by socialization of the newest tax regulation to tax payer. Supervising to Tax officer can be improved by speeding- up the form of supervising committee in taxation.